2004
DOI: 10.3168/jds.s0022-0302(04)73254-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Source and Dietary Level on Zinc Metabolism in Holstein Calves

Abstract: Forty-eight Holstein male calves were stratified by origin and body weight and randomly assigned to one of 4 treatment groups. Dietary treatments were administered in 2 phases. In phase 1, treatment groups received the basal diet with no supplemental Zn (control), basal diet plus 20 mg of Zn/kg of DM as ZnSO4 or Zn proteinate (ZnProt), or basal diet plus 20 mg of Zn/kg of DM with 50% of the Zn supplied from each source (ZnM) for 98 d. In phase 2, calves continued to receive the same Zn source fed in phase 1; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 18 publications
9
57
2
2
Order By: Relevance
“…Kincaid et al (1997) indicated that application in calves' nutrition of zinclysine and zinc-methionine in amount of 300 mg of Zn/kg of feed caused the increase of content of this element in liver in comparison with animals received zinc oxide. The higher zinc content in calves tissues (Wright & Spears 2001) and lambs (Cao et al 2000) indicated also comparison the availability of zinc from zinc-proteinate and zinc sulphate. The application of different forms of zinc changed the pathways of absorption of this element.…”
Section: Discussionmentioning
confidence: 99%
“…Kincaid et al (1997) indicated that application in calves' nutrition of zinclysine and zinc-methionine in amount of 300 mg of Zn/kg of feed caused the increase of content of this element in liver in comparison with animals received zinc oxide. The higher zinc content in calves tissues (Wright & Spears 2001) and lambs (Cao et al 2000) indicated also comparison the availability of zinc from zinc-proteinate and zinc sulphate. The application of different forms of zinc changed the pathways of absorption of this element.…”
Section: Discussionmentioning
confidence: 99%
“…Young calves fed milk replacer tolerated 500 mg Zn/kg diet for five weeks without adverse effects, but 700 mg/kg diet caused a reduction in weight gain, feed intake and feed efficiency (Jenkins and Hidiroglou, 1991). Wright and Spears (2004) administered a diet containing 530 mg Zn (from zinc sulphate, zinc proteinate and a mixture of both zinc sources)/kg diet to Holstein calves for 14 days to evaluate the effects of dose and source on metabolism and zinc tissue concentrations; no adverse effects were recorded. Arelovich et al (2000) administered zinc chloride by ruminal cannulas to provide the equivalent of an additional 30, 250 and 470 mg Zn/kg diet to heifers that were fed prairie hay and urea.…”
Section: Ruminantsmentioning
confidence: 99%
“…Zinc is regulated at the intestinal level in the target animals. With the exceptions of liver and kidney (Eisemann et al, 1979;Jenkins and Hidiroglou, 1991; Cao et al, 2000; Gallaher et al, 2000;Wright and Spears, 2004; see also review of Schlegel et al, 2013), zinc concentrations exceeding the requirements up to about 200 mg/kg feed will not result in a change of zinc concentrations in animal tissues (Jenkins and Hidiroglou, 1991), and other products including milk (Schwarz and Kirchgessner, 1975; Miller et al, 1989;Wiking et al, 2008; Peters and Mahan, 2008; Peters et al, 2010). Consequently, a reduction in dietary zinc in the range between requirements and 150 mg/kg feed will affect zinc concentration only in liver and kidney.…”
mentioning
confidence: 99%
“…Nevertheless, some studies report a higher zinc serum concentration in animals feed a diet supplemented with excess zinc, when compared to a control diet (WRIGHT; SPEARS, 2004).…”
Section: Resultsmentioning
confidence: 99%